Arteriovenous malformation in pancreas mimicking hypervascular tumor. Issue 4 (18th April 2020) - Ishigami, Keisuke; Sakuma, Tomoya; Saito, Masato; Kawakami, Yujiro; Masaki, Yoshiharu; Murota, Ayako; Motoya, Masayo; Kimura, Yasutoshi; Nakase, Hiroshi
Abstract: Arteriovenous malformation (AVM) is defined as a disease that causes blood flow abnormality due to anastomoses of the arteries and veins. AVM can occur in any gastrointestinal tract, but pancreatic AVM (P‐AVM) is very rare. Previous reports demonstrated that contrast‐enhanced CT (CECT) typically showed abnormal vascular network in pancreas. We present a 58‐year old man with a history of acute pancreatitis. He was referred to our hospital for examination of pancreatic mass. CECT showed a round‐shaped hypervascular lesion with a diameter of 8 mm in the head of the pancreas. Selective angiography showed vascular network and early visualization of superior mesenteric vein. We finally diagnosed this case as P‐AVM. He underwent duodenum preserving pancreatic head resection. Histological findings confirmed the preoperative diagnosis of P‐AVM. Abstract : An asymptomatic 58‐year old man with a history of acute pancreatitis was referred to our hospital for examination of a round‐shaped hypervascular lesion with a diameter of 8 mm in the head of the pancreas. Selective angiography showed vascular network in the pancreatic head and super‐selective injections from pancreaticoduodenal artery revealed early visualization of superior mesenteric vein. Pancreatic arteriovenoous malformation typically showed multiple discrete intrapancreatic vessels, and few cases were reported as hypervascular tumorous lesion.